Comparison of the cytotoxicity of cladribine and clofarabine when combined with fludarabine and busulfan in AML cells: enhancement of cytotoxicity with epigenetic modulators - Valdez, Benigno C. (Exp Hematol, 2015)
Clofarabine (Clo), fludarabine (Flu) and busulfan (Bu) combinations are efficacious in hematopoietic stem cell transplantation (HSCT) for myeloid leukemia. We now determined if the more affordable drug cladribine (Clad) can provide a viable alternative to Clo, with or without panobinostat (Pano) and 5-aza-2′-deoxycytidine (DAC). Both [Clad+Flu+Bu] and [Clo+Flu+Bu] combinations showed synergistic cytotoxicity in KBM3/Bu250(6), HL60 and OCI-AML3 cell lines. Cell exposure to these drug combinations resulted in 60%-80% inhibition of proliferation, activation of the ATM pathway, increase in histone modifications, decrease in HDAC3, HDAC4, HDAC5 and SirT7 proteins, decrease in mitochondrial membrane potential, activation of apoptosis and stress signaling pathways, and down-regulation of the AKT pathway. These drug combinations activated DNA-damage response and apoptosis in primary cell samples from AML patients. At lower concentrations of Clad/Clo, Flu and Bu, inclusion of Pano and DAC enhanced cell killing, increased histone modifications and DNA demethylation, and increased the level of P16/INK4a, P15/INK4b and P21/Waf1/Cip1 proteins. The observed DNA demethylating activity of Clad and Clo may complement DAC activity, increase demethylation of the gene promoters for the SFRP1, DKK3 and WIF1, and cause degradation of β-catenin in cells exposed to [Clad/Clo+Flu+Bu+DAC+Pano]. The overlapping activities of [Clad/Clo+Flu+Bu], Pano and DAC in DNA-damage formation and repair, histone modifications, DNA demethylation and apoptosis may underlie their synergism. Our results provide a basis for supplanting Clo with Clad and for including epigenetic modifiers in the pre-HSCT conditioning regimen for myeloid leukemia patients in regions where economic factors might restrict the use of Clad.